Prevalence and Management Recommendations for Disease-Related Malnutrition in Chronic Kidney Disease Patients with and without Diabetes. (25th August 2022) - Dai, Li-Li; Li, Wei-Li; Zheng, Ding-Feng; Wang, Wei-Hong; Xie, Hao-Fen; Ma, Jian-Wei
Abstract : Objective . To investigate the nutritional risk, malnutrition, severe malnutrition, and malnutrition prevalence of different stages in chronic kidney disease (CKD) patients with and without diabetes mellitus using the Global Leadership Initiative on Malnutrition (GLIM), and to analyze the causes of malnutrition and to improve the clinical outcomes of patients for early intervention. Methods . A total of 683 patients with CKD who were hospitalized in our hospital from January 2020 to January 2021 were enrolled and divided into subgroups 1 to 5 according to whether they were complicated with diabetes and glomerular filtration rate. Using the second step of the malnutrition (GLIM) diagnostic tool and 2 previously commonly used malnutrition assessment methods (body mass index <18.5 kg/m 2 with poor general condition, 3 points for nutritional deficiency in nutritional risk screening), combined with clinical research on the main causes of malnutrition, the intervention measures were discussed. Results . The prevalence of malnutrition was 16.7% (114/683) in the patients included in the survey using the diagnostic criteria of malnutrition (GLIM) (excluding whole body muscle mass index). The prevalence of malnutrition in CKD patients with and without diabetes was 23.7% and 12.6%, respectively. The overall prevalence rate of severe malnutrition was 14.2%, and the prevalence rates of those with and without diabetes were 19.0% and 11.4%, respectively; the results of the two methods of malnutrition assessment showed that the prevalence of malnutrition in CKD patients with diabetes was higher than that in the uncombined group. There was no severe malnutrition in patients with CKD stages 1 and 2. From CKD stage 3 onwards, the severe malnutrition in the diabetic group was significantly higher than that in the uncombined group. Conclusion . With the progression of CKD, the incidence of malnutrition also gradually increased, indicating that malnutrition is related to primary diseases and concomitant diseases. Attention should be paid to the malnutrition of CKD patients with diabetes, and clinical medical staff need to pay early attention to various diseases that lead to the progression of CKD, such as diabetes, primary nephropathy, and other factors, to prevent complications and delay the progression of CKD.